Fatty Acid Triangulation in Albumins Using a Landmark Spin Label. Issue 11 (18th November 2019) - Reichenwallner, Jörg; Hauenschild, Till; Schmelzer, Christian E. H.; Hülsmann, Miriam; Godt, Adelheid; Hinderberger, Dariush
Abstract: Several spatial correlations of up to six fatty acid (FA) binding sites in albumins were found by double electron‐electron resonance (DEER). A strategy was used that combines spin‐labeling and spin‐probing techniques in electron paramagnetic resonance (EPR) spectroscopy. This is here achieved by introducing an additional covalent landmark spin (LS) label to the self‐assembled system of EPR‐active, paramagnetic stearic acid derivatives and albumins. Therefore, a cysteine specific, paramagnetic LS that was attached to the albumin surface at a unique position (Cys34) provides a fixed topological reference point for monitoring statistical ligand uptake. We propose that the determination of nanoscale distance distributions emerging between the LS and EPR‐active fatty acid derivatives generally allows for the direct observation of individually occupied binding sites in solution. Essentially, several binding pockets, groups of them and evidence for ligand‐induced allosteric modulation can be traced from such FA‐LS interspin correlations. Experimental results were substantiated with theoretical predictions from molecular dynamics (MD) simulations. It was observed that all binding sites in an albumin ensemble may be statistically filled even at the lowest level of ligand loading. This approach generally bears the potential for mapping occupation states of individual ligand binding sites in proteins using such spin‐labeled ligands. Abstract :